Silage based feeding system for goats - Kumar, Ravindra; Arif, Mohd.; Kumar, Arvind (Indian Farming, 2024)
Due to decline of grazing pasture, the goat farmers are shifting to stall feeding of goat with concentrate mixture, straw and green fodder particularly in peri urban locality. Green fodders are not available round the year like in summer season. So fodder like maize can be preserved as silage and fed to goats when green fodder or grazing pasture is not available. Goats can be well reared with silage and concentrate feeding. Experiments were conducted at ICAR-Central Institute for Research on Goats and it was reported that both growing and lactating goats can be reared with concentrate and silage feeding under stall feeding condition. If pasture in grazing area is not proper, silage can be a good alternative for goats especially in production situation that require good nutrient support.